El verano en que mi madre tuvo los ojos verdes de Tatiana Țîbuleac: El trauma y la mirada / The Summer when my Mother had Green Eyes by Tatiana Țîbuleac: the trauma and the gaze - Alexandrescu, Ioana (Swedish Journal of Romanian Studies, 2020)
”The Summer when my Mother had Green Eyes” is Moldovan writer Tatiana Țîbuleac’s first novel and it was praised by both readers and critics. We examine the Spanish version of this novel, which was published in 2019 by Madrid-based publishing house Impedimenta and has reached its fifth edition in less than a year. The design of this novel alternates short chapters and micro chapters consisting of a sole phrase, as well as sarcastic and poetic tonalities, and reconstructs the narrator's relationship with his dying mother during the last summer they spend together in a French village close to the ocean.